PENGARUH KUALITAS INFORMASI PADA SIKAP TERHADAP MEREK HEXA IMAGES - Sulistiani, Putri Budi (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
Abstract This study examines the influences of information quality and attitude toward brand. This study uses Hexa Images as the object of the study. Hexa Images is a multimedia services company especially for Wedding project. This study analyze Hexa Images’s Instagram account as one of its marketing tools. Using Quantitative and AMOS-SEM used for research analysis methods. Data collection through direct questionnaire with the criteria of respondent are male or female who is already plan for wedding in a short time. The measured variable in this study is that information quality and attitude toward brand were measured using a 5-point Likert scale. This study found that information quality has an influence of attitude toward brand, Keywords: information quality, attitude toward brand, social media, Instagram.